(untitled) (The Research of Medical Science Review, 2024)
This study investigates the role of nurse-led cardiac rehabilitation in promoting health behavior changes among patients recovering from myocardial infarction. It highlights how structured rehabilitation programs, facilitated by nursing professionals, can enhance patient outcomes by fostering lifestyle modifications such as improved diet, increased physical activity, and better medication adherence. The research employs a mixed-methods approach, combining quantitative assessments of health behavior changes with qualitative interviews to gather patient experiences. Findings indicate that nurse-led interventions not only support physical recovery but also empower patients to take an active role in their health management. This study emphasizes the importance of integrating nursing expertise into cardiac rehabilitation programs to optimize recovery and long-term health for myocardial infarction patients.